(untitled) (Journal of the College of Basic Education, 2023)
The study aimed to identify the effect of visual compound exercises in the two variable stylesAnd random to develop the accuracy and speed of motor response in some of the technical skills of football playersVolleyball for youth ages 16-181 (years old); Use the experimental method for its suitability to naturesearch; The research sample consisted of the police club players and the third and adult football teamThey have (0! players) divided into two groups, each group (10) players usedThe first group (visual compound exercises with a variable exercise method), which is a groupThe third Karkh breeding team, while the second group, the Police Club group, was used(Visual composite exercises randomly styled); The program implementation period continued (10).weeks, at the rate of three training units per week; These exercises were performed at the beginning of the sectionthe principal of the educational unit; After implementing the educational program, the researchers concluded that there isA development occurred between the two groups in favor of the post-tests in the research tests; WhileNo significant differences were achieved between the two groups in the post tests.